Nonlinear Photonics and Novel Optical Phenomena - Chen, Zhigang; Morandotti, Roberto; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Nonlinear Photonics and Novel Optical Phenomena contains contributed chapters from leading experts in nonlinear optics and photonics, and provides a comprehensive survey of fundamental concepts as well as hot topics in current research on nonlinear optical waves and related novel phenomena. The book covers self-accelerating airy beams, integrated photonics based on high index doped-silica glass, linear and nonlinear spatial beam dynamics in photonic lattices and waveguide arrays, polariton solitons and localized structures in semiconductor microcavities, terahertz waves, and other novel phenomena in different nanophotonic and optical systems.
Chapter 1 - Self-Accelerating Airy Beams: Generation, Control, and Applications -- Chapter 2 - Advanced Integrated Photonics in Doped Silica Glass -- Chapter 3 - Linear and Nonlinear Wave Behavior in Amorphous Photonic Lattices -- Chapter 4 - Nonlinear Control of Multi-Color Beams in Coupled Optical Waveguides -- Chapter 5 - Spatial Beam Dynamics Mediated by Hybrid Nonlinearity -- Chapter 6 - Theory of Polariton Solitons in Semiconductor Microcavities -- Chapter 7 - Observation of (3z(BTrue(3y (BOptical Vortices in a Laser System -- Chapter 8 - Scale-Free Optics -- Chapter 9 - Spatially Dispersive Shock Waves in Nonlinear Optics -- Chapter 10 - Nonlinear Interaction of Intense Ultrashort Filaments -- Chapter 11 - The Dawn of Ultrafast Nonlinear Optics in the Terahertz Regime -- Chapter 12 - Generation of Terahertz Radiation via Purcell Enhanced Nonlinear Frequency Mixing -- Chapter 13 - Photonic Transition in Nanophotonics.s
Keywords: Physics; Microwaves; Optical materials; Physics; Optics and Electrodynamics; Optical and Electronic Materials; Microwaves, RF and Optical Engineering; Optics, Optoelectronics, Plasmonics and Optical Devices; Nanoscale Science and Technology